Molecular and cellular determinants of L-Dopa-induced dyskinesia in Parkinson’s Disease - Servillo, Federica; De Carluccio, Maria; Di Lazzaro, Giulia; Campanelli, Federica; Marino, Gioia; Natale, Giuseppina; Ledonne, Ada; Massaro Cenere, Mariangela; Paldino, Emanuela; Di Giuda, Daniela; Picca, Anna; Bove, Francesco; et al. (NPJ Parkinson's Disease, 2024)
Treatment with L-3,4-dihydroxyphenylalanine (L-Dopa) compensates for decreased striatal dopamine (DA) levels and reduces Parkinson’s disease (PD) symptoms. However, during disease progression, L-Dopa-induced dyskinesia (LID) develops virtually in all PD patients, making the control of PD symptoms difficult. Thus, understanding the mechanisms underlying LID and the control of these motor abnormalities is a major issue in the care of PD patients. From experimental and clinical studies, a complex cascade of molecular and cellular events emerges, but the primary determinants of LID are still unclear. Here, with a translational approach, including four animal models and a wide cohort of PD patients, we show that striatal DA denervation is the major causal factor for the emergence of LID, while α-synuclein aggregates do not seem to play a significant role. Our data also support the concept that maladaptive basal ganglia plasticity is the main pathophysiological mechanism underlying LID.